Small business enterprises: Strategies for the 1980s - Ernst W. Neuland (South African Journal of Business Management, 1982)
The importance of small business enterprises in a free market economy is reflected by their contribution to economic activity, maintaining competitiveness, and provision of employment opportunities. Despite their economic importance, small business firms are characterized by a high failure rate, inter alia, owing to their unique problems. The independent entrepreneur accordingly has a definite need for aid - which is rendered to the small business sector in the majority of capitalistic countries, including South Africa. It would appear that research in the field of small business has, almost without exception, been conducted in an unsystematic and fragmentary manner. In this paper a conceptual framework, which is based on the developmental approach and the life cycle concept, is advanced. By relating the specific problems of small business firms to the stage of development of the firm in a strategic sense, a systematic approach for studying the dynamic small business firm ensues. This approach will also serve as a conceptual framework for: research into small business firms; developmental aid to the small business sector; development and training of entrepreneurs; financing considerations by the financial sector; and strategy formulation and implementation for the small business firm as such.
Keywords: 650